162k views
1 vote
Q1: If r = 9, b = 5, and g = -6, what does (r + b - g)(b + g) equal?

-14

-20

220

154


Q2: If 9(x - 9) = -11, then x = ?

70/9

108

-2/9

-90

(The images are 2 more questions)

Q1: If r = 9, b = 5, and g = -6, what does (r + b - g)(b + g) equal? -14 -20 220 154 Q-example-1
Q1: If r = 9, b = 5, and g = -6, what does (r + b - g)(b + g) equal? -14 -20 220 154 Q-example-1
Q1: If r = 9, b = 5, and g = -6, what does (r + b - g)(b + g) equal? -14 -20 220 154 Q-example-2
User Sebbab
by
6.6k points

1 Answer

2 votes

Answer:

Q1 is -20.

i dont know the rest. it will take a sec

User Cemal
by
6.1k points